2022
DOI: 10.1111/febs.16688
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates tumour characteristic RNA modifications in ovarian cancers

Abstract: Analysis of ovarian cancer tissue and normal ovarian tissue revealed 31 RNA modifications with significant differences observed in cancer tissue compared with normal tissue. Moreover, we found Im and chm5U as characteristic RNA modifications in advanced and platinum‐resistant ovarian cancers, respectively. Considering that these differences in RNA modifications may be due to the intra‐tumour microenvironment, we xenografted the ovarian cancer cell line RMG‐1 to create RMG‐1 tumours and compared them with origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…M7G Currently, METTL1 is the most well-recognized m7G regulator, which binds with its cofactor, WD repeat domain 4 (WDR4), to catalyze m7G modifications in tRNA, miRNA, and mRNA [134]. m7G has a pivotal role in several types of tumors, including gliomas, ovarian cancers, certain sarcomas, breast cancers and so on [9,[135][136][137]. Li et al [138] found that METTL1 may promote the malignant behavior of glioma cells through the MAPK signaling pathway.…”
Section: Ybx1 (Yb-1)mentioning
confidence: 99%
“…M7G Currently, METTL1 is the most well-recognized m7G regulator, which binds with its cofactor, WD repeat domain 4 (WDR4), to catalyze m7G modifications in tRNA, miRNA, and mRNA [134]. m7G has a pivotal role in several types of tumors, including gliomas, ovarian cancers, certain sarcomas, breast cancers and so on [9,[135][136][137]. Li et al [138] found that METTL1 may promote the malignant behavior of glioma cells through the MAPK signaling pathway.…”
Section: Ybx1 (Yb-1)mentioning
confidence: 99%